Union of the Comoros : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This report provides a summary of the Antimoney Laundering and Combating the Financing of Terrorism (AML/CFT) measures in effect in the Union of the Comoros on the date of or shortly after the onsite visit. It describes and analyzes these measures, indicates the level of the Union of the Comoros's compliance with the 40 + 9 Financial Action Task Force (FATF) Recommendations, and makes recommendations on measures to be taken to strengthen certain aspects of the system. The authorities agreed with the mission that the Comoros is a potential transit point for international terrorism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet